ULTRASOUND CHARACTERISTICS OF ACUTE AND CHRONIC ODONTOGENIC SUBMANDIBULAR LYMPHADENITIS IN CHILDREN - Ksonz, I.V. (World of Medicine and Biology, 2015)
Summary. The aim was to study the characteristics of the ultrasound picture of acute and chronic purulent hyperplastic odontogenic submandibular lymphadenitis in children.The study analyzed survey of 40 patients with acute purulent odontogenic submandibular lymphadenitis and 10 children with chronic hyperplastic odontogenic submandibular limfadenti aged 7 to 12 years.Patients with acute purulent lymphadenitis were divided into 2 groups: 1 - children who have lymph node inflammation coincided with exacerbation of chronic granulating periodontitis temporary molars of the lower jaw and which according to our beliefs, became the causative factor in its occurrence; 2 - children who have established the presence of temporary molars affected by chronic periodontitis in remission. In the middle of each group, the patients were divided into subgroups depending on length of seeking medical care from the onset.To groups include 10 control healthy children who for review and conclusion pediatrician that last 2 months not hurt acute infectious diseases and did not use any drugs.The assessment of hemo circulation indicators in the Doppler scan in patients who applied on the first day of the appearance of the first clinical signs of inflammation, revealed a significant increase values of resistance index of 2.9 and pulsating index of 3.8, and especially the final diastolic speed of 13.2 times. These patients when referring to the 2-3 days of onset of clinical signs of inflammation were less pronounced upward trend, but still significantly different from the norm, and is resistant index rose 2.5, Pulse Index 2.0 times final diastolic velocity of 6.8 times.The ultrasound submandibular lymph nodes in chronic hyperplastic lymphadenitis odontogenic characterized by the following parameters: transverse size was 1,09 ± 0,10 cm .; anteroposterior size made 1,73 ± 0,10 cm .; the ratio of the cross and anteroposterior dimension (index Solbiati) reached 0,63 ± 0,05; image gate - present; cortex visualized; degree was mixed echogenicity, namely izoechogenic cases were 60%, 40% were hyperechoic; resistance index has averaged 0,39 ± 0,04; pulsation index is 0,54 ± 0,06; end diastolic velocity was 3,08 ± 0,54 cm / s.The data analysis of the Doppler scan in patients with acute purulent submandibular limfadentit, revealed that the duration from the onset to appeal for help, and the type of probable etiological factor significantly affects the nature of violations hemo circulation stream The degree of blood flow is directly dependent on the terms that share the primary clinical manifestations and treatment time with. How is it less prolonged, the greater the intensity of blood circulation in the area of inflammation, which creates better conditions for reparative regeneration after surgery. Sonographic picture of chronic hyperplastic odontogenic submandibular lymphadenitis characterized by increasing size, hyperechogenicity and increased peripheral vascular resistance component
Keywords: ultrasonography; children; submandibular lymphadenitis